232k views
3 votes
Full working out please ^^ for the first question , ty

Full working out please ^^ for the first question , ty-example-1

1 Answer

6 votes

Answer:

E

Explanation:

Given

y = 2x² - kx + 3

with a = 2, b = - k and c = 3

Since the curve touches the x- axis at one place then the roots are real and equal and the discriminant for this condition is

b² - 4ac = 0, that is

(- k)² - (4 × 2 × 3) = 0

k² - 24 = 0 ( add 24 to both sides )

k² = 24 ( take the square root of both sides )

k = ±
√(24) = ± 2
√(6)

k = 2
√(6) or k = - 2
√(6) → E

User Chenaren
by
5.5k points